(untitled) - Chand, Attar (New Delhi, 1979)
The major aim of this bibliography, though selective, is to list together the most signficant books and periodical articles that appeared during the last thirty years (1947 - 1977) in other to provide a base for futher researches, discussion and comprehensive analysis of the subject.
Keywords: Đông Á,East Asia; Thư mục,Bibliography